Small Gas Molecules on Functionalized Single-Walled Carbon Nanotubes: Gas Sensor Application - Chanajaree1, Rungroj; Wittayanarakul2, Kitiyaporn (Asian Journal of Chemistry, 2014)
The quantum mechanical calculations with own N-layered Integrated molecular orbital and molecule mechanics (ONIOM) method have been conducted to investigate the interactions between the small gases (i.e., hydrogen and oxygen) and the functionalized (8,8) single-walled carbon nanotubes (SWCNTs). The role of tip functionalizations of single walled carbon nanotube (SWCNTs) on gas adsorption has been determined. As the results, the hydrogen molecule can be well adsorbed by the SWCNT with positive charge functionalization, while the oxygen molecule prefers to adsorb on the non-functionalized SWCNT. Moreover, it appears that H2 molecule binding with positive charged carbon nanotube (CNT+) in the vertical direction is the most favorable because the average binding energy is equal to -18.5 ± 4.4 kcal/mol. Although, the average binding energy between H2 molecule with negative charged carbon nanotube (CNT–) in the vertical is -19.9 ± 7.0 kcal/mol, its standard deviation is greater than the standard deviation of H2 molecule binding with CNT+ in the vertical direction. In addition, O2 molecule binding with carbon nanotube in the vertical direction is the most favorable because the average binding energy is equal to -48.3 ± 6.4 kcal/mol. This theoretical investigation provides information which will be very useful for development of gas sensors.